VERBAL AND NON-VERBAL EXPRESSIONS IN THE TRADITION OF MOMBOLASUAKO OF TOLAKI - Ilfan Askul Pehala; Inyo Yos Fernandez; Wakit Abdullah (Center of Language and Cultural Studies [CLCS], 2017)
This research aims to classify, describe and explain verbal and non-verbal expressions in eloping tradition (mombolasuako) of Tolaki based on the procession comprehensively. Theories used to solve the problem are ethnolinguistics and ethnoscience. Methodologically, the ethnographic method was used in this study. The data includes primary and secondary data that were collected by participant observation and an in-dept interview. All collected data were analyzed by using Spradely ethnoscience’s analysis and linguistics’ analysis. The study revealed that verbal expressions in mombolasuako include verbal utterances, recitation and remark. The non-verbal expressions consisted of (1) the tradition objects must be served by bride groom consists of process (2) gestures of tradition casts in the implementation of the traditions process and (3) tradition casts. The mombolasuako’s process of verbal and non-verbal expressions including verbal utterances, gestures and tradition casts were adapted to tradition.